A systematic review of Green Business Process Management. Issue 2 (25th November 2019) - Couckuyt, Dries; Van Looy, Amy
Abstract : Purpose: Green Business Process Management (BPM) focusses on the ecological impact of business processes. Although it is an emerging field, different attitudes exist towards the discipline's name, the objectives and the approaches to realise them. By means of a systematic literature review, the purpose of this paper is to arrive at a common understanding of the discipline for successful development. Design/methodology/approach: The review methodology relies on a hermeneutic framework which integrates the search, analysis and interpretation of the literature. The sample is used in a text analysis to find an appropriate definition ( RQ1 ), a bibliometric analysis to give insights in current Green BPM contributions ( RQ2 ) and a content analysis to present differences with conventional BPM ( RQ3 ). Findings: Green BPM follows a similar development as conventional BPM, namely from a more technical perspective to also including the managerial perspective. More research is required that goes beyond the traditional business process lifecycle. Originality/value: The research questions generated a comprehensive overview about application domains and research topics, which in turn can deliver benefits for both research and practitioner-related communities. Researchers identify future research avenues, while practitioners find appropriate Green BPM techniques for their domain.